2020
DOI: 10.3389/fendo.2020.00531
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Serum Leptin, Adiponectin, Interleukin-6, and Visfatin Are Altered in Chinese Children With Febrile Seizures: A Cross-Sectional Study

Abstract: Adipokines, including leptin, visfatin, adiponectin, and interleukin-6 (IL)-6, play multiple roles in the pathophysiology of epilepsy and febrile seizures (FS). We aimed to investigate the associations among plasma adipokines, mainly leptin, visfatin, adiponectin, or IL-6, and the prognosis of FS. This prospective cross-sectional study was conducted from January 2017 to December 2018 at the Wuxi Second People' Hospital China. The levels of serum leptin, visfatin, adiponectin, and IL-6 in 55 children with FS (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 46 publications
(60 reference statements)
3
21
0
Order By: Relevance
“…Across the world, the difference between IL-6 levels in children with FSs and fever without seizures has shown conflicting results. 1 2 3 4 7 8 9 Similar to our study, Choi et al observed that serum IL-6 levels in FSs were increased 1.8-fold when compared with FCs, but it was not statistically significant ( p = 0.07). 4 Güven et al also found no significant difference ( p = 0.66) in serum IL-6 levels between FS and FC groups which is similar to our study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Across the world, the difference between IL-6 levels in children with FSs and fever without seizures has shown conflicting results. 1 2 3 4 7 8 9 Similar to our study, Choi et al observed that serum IL-6 levels in FSs were increased 1.8-fold when compared with FCs, but it was not statistically significant ( p = 0.07). 4 Güven et al also found no significant difference ( p = 0.66) in serum IL-6 levels between FS and FC groups which is similar to our study.…”
Section: Discussionsupporting
confidence: 85%
“…3 7 Advancement in molecular biology has led to increased interest in identifying the biomarkers for predicting or diagnosing FS. 1 IL-6 is often considered as key cytokine in the generation of FSs. 5 However, the published scientific literature has often failed to support this view as the results of IL-6 role in FS is inconsistent among various studies across the world.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human studies revealed that serum adiponectin levels are significantly lower in patients with epilepsy than among healthy controls [ 70 , 71 ]. Interestingly, serum/plasma adiponectin levels are elevated in children with febrile seizures and in adults 24 h after a seizure episode [ 72 , 73 ]. These findings suggest that elevated adiponectin at least partially released during primary or secondary generalized tonic-clonic seizures from skeletal muscle may play an anti-inflammatory role, thereby reducing brain damage caused by seizures.…”
Section: Discussionmentioning
confidence: 99%